Drug-Free Approach To Study the Unusual Cell Cycle of Giardia intestinalis - Kathleen Horlock-Roberts (American Society for Microbiology, 2017)
ABSTRACT Giardia intestinalis is a protozoan parasite that causes giardiasis, a form of severe and infectious diarrhea. Despite the importance of the cell cycle in the control of proliferation and differentiation during a giardia infection, it has been difficult to study this process due to the absence of a synchronization procedure that would not induce cellular damage resulting in artifacts. We utilized counterflow centrifugal elutriation (CCE), a size-based separation technique, to successfully obtain fractions of giardia cultures enriched in G1, S, and G2. Unlike drug-induced synchronization of giardia cultures, CCE did not induce double-stranded DNA damage or endoreplication. We observed increases in the appearance and size of the median body in the cells from elutriation fractions corresponding to the progression of the cell cycle from early G1 to late G2. Consequently, CCE could be used to examine the dynamics of the median body and other structures and organelles in the giardia cell cycle. For the cell cycle gene expression studies, the actin-related gene was identified by the program geNorm as the most suitable normalizer for reverse transcription-quantitative PCR (RT-qPCR) analysis of the CCE samples. Ten of 11 suspected cell cycle-regulated genes in the CCE fractions have expression profiles in giardia that resemble those of higher eukaryotes. However, the RNA levels of these genes during the cell cycle differ less than 4-fold to 5-fold, which might indicate that large changes in gene expression are not required by giardia to regulate the cell cycle. IMPORTANCE Giardias are among the most commonly reported intestinal protozoa in the world, with infections seen in humans and over 40 species of animals. The life cycle of giardia alternates between the motile trophozoite and the infectious cyst. The regulation of the cell cycle controls the proliferation of giardia trophozoites during an active infection and contains the restriction point for the differentiation of trophozoite to cyst. Here, we developed counterflow centrifugal elutriation as a drug-free method to obtain fractions of giardia cultures enriched in cells from the G1, S, and G2 stages of the cell cycle. Analysis of these fractions showed that the cells do not show side effects associated with the drugs used for synchronization of giardia cultures. Therefore, counterflow centrifugal elutriation would advance studies on key regulatory events during the giardia cell cycle and identify potential drug targets to block giardia proliferation and transmission.